PENGARUH LATIHAN IMAGERY TERHADAP KETEPATAN SHOOTING FUTSAL - Muhamad Khalid Yusup; Firman Aditiyatama; Muh Ikhwan Iskandar (Journal of Physical Education and Sport Science, 2019)
This study aims to determine the effect of mental imagery training on shooting accuracy in men's futsal extracurricular at SMK Negeri 3 Kuningan. This type of research is an experiment with the design "The One Group Pretest-Posttest Design". The population in this study were 30 male futsal players at SMK Negeri 3 Kuningan. The sampling technique used purposive sampling, with the following criteria: (1) had participated in a district / city level tournament, (2) the players were students of SMK Negeri 3 Kuningan with an age range of 16-18 years, (3) were male, ( 4) the minimum length of exercise is 6 months. Based on these criteria, 15 people are eligible. The instrument used to measure the accuracy of shooting was shoot on target. The data analysis used the 5% significance level test. The results showed that "there is a significant effect of training on the accuracy of shooting at the men's futsal extracurricular at SMK Negeri 3 Kuningan"